2014
DOI: 10.1007/s13679-013-0087-2
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequalities in Obesity Persist in the Nordic Region Despite Its Relative Affluence and Equity

Abstract: Social inequalities in overweight and obesity (OWOB) have persisted in the affluent and reputedly egalitarian Nordic countries. In this review we examine associations between socioeconomic position (SEP) and OWOB, and secular trends in such associations. Determinants and possible causes of the relations are discussed together with opportunities to cope with OWOB as a public health problem. The findings show a persisting inverse social gradient. An interaction between SEP and gender is noted for adults in Denma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 84 publications
8
56
1
1
Order By: Relevance
“…Unfortunately, we did not have information about the timing of the family break-up or the introduction of the stepfamily members which would have been an interesting addition regarding the timing of the unfavourable weight development. 6,17 In accordance with other studies, 3,30 we found an association between parental educational level and the BMI in their offspring.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, we did not have information about the timing of the family break-up or the introduction of the stepfamily members which would have been an interesting addition regarding the timing of the unfavourable weight development. 6,17 In accordance with other studies, 3,30 we found an association between parental educational level and the BMI in their offspring.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of OW and OB at different time points found in this study is in line with prevalence documented in other Norwegian studies conducted in similar periods among comparable samples . The increase in the prevalence of OW and OB over time has also been previously documented . The findings of the present study indicated an increase in BMI across all percentile groups, significantly more pronounced for the upper percentiles and minimal in the lower percentiles.…”
Section: Discussionsupporting
confidence: 92%
“…For Scotland, reports suggested that societal changes and technological developments have created an obesogenic environment over time that impedes to maintain healthy weight [49,50]. Nordic countries are changing towards a less regulated marketliberalism potentially leading to an increased risk in obesity by a rise in fast-food industry in combination with a more stressful life [51]. While our findings on Scotland are in line with other studies, we were not able to find evidence why Scotland fared worse in the obesity epidemic.…”
Section: Discussionmentioning
confidence: 99%